2020
DOI: 10.3762/bjoc.16.49
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed remote C–H arylation of polycyclic aromatic hydrocarbons (PAHs)

Abstract: The regioselective C–H arylation of substituted polycyclic aromatic hydrocarbons (PAHs) is a desired but challenging task. A copper-catalyzed C7–H arylation of 1-naphthamides has been developed by using aryliodonium salts as arylating reagents. This protocol does not need to use precious metal catalysts and tolerates wide variety of functional groups. Under standard conditions, the remote C–H arylation of other PAHs including phenanthrene-9-carboxamide, pyrene-1-carboxamide and fluoranthene-3-carboxamide has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The desired product 37c was obtained through a plausible six-membered metalacyclic intermediate 37d, followed by aryl migration. You et al revealed [103] an example of Cu-catalyzed C9 arylation of pyrene-1-carboxamide (37e) with mesityl(phenyl)iodonium triflate (37f) through a bidentate 8-aminoquinoline system, affording 37g (Scheme 30). Substrate N-(tert-butyl)pyrene-1-carboxamide 37e was treated with mesityl(phenyl)iodonium triflate in the presence of Cu(OTf) 2 (10 mol%) in 1,2-dichloroethane at 70 • C for 24 h. This reaction afforded the C(9)-arylated pyrene-1-carboxamide derivative 37g of 65%.…”
Section: Directing Group-assisted C-h Functionalization Of the C9 Pos...mentioning
confidence: 99%
“…The desired product 37c was obtained through a plausible six-membered metalacyclic intermediate 37d, followed by aryl migration. You et al revealed [103] an example of Cu-catalyzed C9 arylation of pyrene-1-carboxamide (37e) with mesityl(phenyl)iodonium triflate (37f) through a bidentate 8-aminoquinoline system, affording 37g (Scheme 30). Substrate N-(tert-butyl)pyrene-1-carboxamide 37e was treated with mesityl(phenyl)iodonium triflate in the presence of Cu(OTf) 2 (10 mol%) in 1,2-dichloroethane at 70 • C for 24 h. This reaction afforded the C(9)-arylated pyrene-1-carboxamide derivative 37g of 65%.…”
Section: Directing Group-assisted C-h Functionalization Of the C9 Pos...mentioning
confidence: 99%
“…Very recently, You and co-workers extended the concept of copper-catalyzed meta C−H arylation of amine derivatives and aryl acetic acid derivatives for the remote C−H arylation of substituted polycyclic aromatic hydrocarbons (PAHs) like substituted 1-napthamides phenanthrene-9-carboxamide, pyrene-1-carboxamide, and fluoranthene-3-carboxamide, among others, using aryliodonium salts as the arylating agent (Scheme 41). 122 The protocol was not only limited to the amide directing group; additionally, their ketone derivatives were found to be suitable for the C−H arylation with moderate yields. The reaction proceeded through a similar pathway as proposed by Wu, Li, and their co-workers.…”
Section: C−h Alkylation Since the Pioneering Work On The [Ru]-catalyz...mentioning
confidence: 99%
“…In 2020, You research group has reported Cu(II)‐Catalyzed C‐7 arylation of polyaromatic hydrocarbons employing title electrophile (Scheme 26). [58] The C‐7 arylation of different N ‐( tert ‐butyl)‐1‐naphthamide was performed with unsymmetrical iodonium triflate using 10 mol % Cu(OTf) 2 in DCE at 70 °C. The yields of arylation were influenced by electronic effects as well as the steric effect of diverse aryliodonium salts based on the substituents on the aryl ring.…”
Section: C(sp2)−h Arylation Reactionmentioning
confidence: 99%